Geological Setting and Solid Mineral Potentials of Southern Borno, Northeastern Nigeria - Baba, S.; Shettima, B.; Kamale, H.I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This research work has principally succeeded in updating the geological map of Southern Borno and brought out zeolite as one of the prominent solid minerals to work on. The field mapping of the area constituting of Askira Uba, Bayo, Biu, Chibok, Damboa, Gwoza, Hawul, KwayaKusar, and ShaniLocal Government Areas indicate the occurrence of basement and sedimentary rocks. The crystalline rocks comprises of migmatites, gneisses, granites and basaltic rocks, dominantly occurring in Gwoza, AskiraUba, Chibok, Biu and Hawul, whereas the sedimentary formations cover KwayaKusar, Shani, Bayo and Damboa with outcrops of Cretaceous-Quaternary sediments comprising Bima Formation, Gongila Formation, Fika Shales, Gombe Sandstone, Kerri Kerri Formation and Chad Formation. Mineralogical evaluation of the Basement Complex rocks indicate the occurrences of feldspars, quartz, micas and ornamental stones, with the basalts chiefly hosting zeolite and quality gemstones (aquamarine, corundum, amethyst, tourmaline and topaz). The zeolites are typical of chabazite variety mostly developing from feldspathoid associated with mafic igneous/basic volcanic rocks. The Cretaceous-Quaternary sediments present quality clays, kaolinite, diatomite, trona and bentonite industrial minerals.